2017
DOI: 10.1515/jpem-2016-0201
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal testosterone gel for induction and continuation of puberty in adolescent boys with hepatic dysfunction

Abstract: Treatment to induce puberty in boys is indicated in those who do not undergo spontaneous development at a normal age. Stimulating development of the secondary sex characteristics is possible using gradually increasing doses of testosterone esters (TEs) via intramuscular (IM) administration, which is the most widely used method of testosterone (T) supplementation. When TEs are administered as monthly injection, serum T levels exhibit large fluctuations with supraphysiologic levels seen immediately after the inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Similarly, 1% testosterone gel was effective in promoting secondary sexual characteristics in boys affected with Klinefelter's syndrome [54]. Recently, testosterone transdermal gel preparations in strengths of 1% and 2% were found to be safe and effective on adolescent hypogonadal boys with concomitant hypertransaminasemia [55]. Another recent study on boys affected with CDGP has reported equal efficacy of testosterone transdermal gel 2% and intramuscular testosterone in comparison to untreated subjects in increasing height velocity [56].…”
Section: Testosteronementioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, 1% testosterone gel was effective in promoting secondary sexual characteristics in boys affected with Klinefelter's syndrome [54]. Recently, testosterone transdermal gel preparations in strengths of 1% and 2% were found to be safe and effective on adolescent hypogonadal boys with concomitant hypertransaminasemia [55]. Another recent study on boys affected with CDGP has reported equal efficacy of testosterone transdermal gel 2% and intramuscular testosterone in comparison to untreated subjects in increasing height velocity [56].…”
Section: Testosteronementioning
confidence: 98%
“…Maximum Dose 100 mg [46,60] Adult dosage: 150-200 mg every 2weeks [61] T. Undecanoate IM Injection No data available For puberty induction, only in young men [62] Adult dosage: 750-1000 mg every 10-14weeks [61,62] T. Transdermal gels 10 mg daily for 3 months [56] Gel 1%: 0.5 g/day, increased up to 5 g/day as needed [54]. Adult dosage: 5-10 g/day [61] Gel 2%: Initial dose 10 mg/day [55]. Adult dosage: 40-70 mg/day [61] T. Undecanoate Oral tablets Initial dose 40 mg daily, Maximum dose 80 mg twice daily [51] Adolescent Population: No data 40 mg daily for 4 weeks [50] 40 mg daily for 3 months [52] Adult with hypogonadism , maximum dose is 80 mg twice daily [51] 20 mg daily for 6 months [63] 40 mg daily for mean of 3.5 months [64] T. Transdermal patches Age 12.5 to 15 years: 5 mg over 8-12 hours for 8 weeks [65] Pre-pubertal 14-16 years: 2.5 mg over 12 hours overnight [65] Partially virilized 17-19 years: 2.5 mg daily [65] Virilized men above 20 years: 5 mg daily [53] T. Pellets Subcutaneous No Data Available 13.9 to 17.5 years: 8-10 mg/Kg every 6 months for three doses [53] T…”
Section: Cdgp Hypogonadismmentioning
confidence: 99%
“…Out of the included studies one was a questionnaire based survey, 49 two were clinical trials, 50,51 and one a retrospective case reports review 52 one a case report. 53 This is an explicit manifestation of the dire insufficiency of clinical trials and on young males with TE requirements.…”
Section: Study Selectionmentioning
confidence: 99%
“…It can be seen that both gel and IM TE preparations are able to achieve desirable levels of TE within a short duration with minimal fluctuations. [50][51][52][53] Studies on adult men [54][55][56][57] have reported an average level of TE levels are reported by the weekly usage of short acting IM TE. Women and girls studies 32,[58][59][60][61] reports the favorable pharmacokinetic profile of transdermal gel compared to achieve an optimal peak of TE level.…”
Section: Serum Testosterone Levelmentioning
confidence: 99%
“… 1 Alternative approaches include oral androgens such as testosterone undecanoate 40 and transdermal gels. 41 , 42 …”
Section: Treatmentmentioning
confidence: 99%